Penerapan Spatial Autoregressive Model (SAR) untuk Menentukan Faktor-Faktor Penyebab Kemiskinan di Jawa Barat - 10060118104, Muhammad Reinaldy Tifasi; Marizsa Herlina (UNISBA Press, 2024)
Abstract. Spatial Autoregressive Model (SAR) is an approach model for spatial regression analysis. Spatial regression analysis is used to determine a relationship based on attribute information and location or geographic location information. The estimator of the SAR model uses the Maximum Likeli hood Estimation (MLE) method. The aim of this research is to model SAR spatial regression to determine the factors that influence the occurrence of poverty in West Java. To explain the spatial relationship between observation locations, a spatial weighting matrix based on neighborhood (contiguity) is used, namely the Queen Contiguity matrix. A total of 27 districts/cities were used as observation units with the dependent variable (Y) being the number of poverty cases from each district/city in West Java. The independent variables used are suspected factors related to poverty cases. The independent variables (X) are the average wage of formal workers, the percentage of the population without a diploma, the percentage of population health, the population, total expenditure per capita, the percentage of open unemployment rate, and the West Java UMR. The independent variables that have a significant effect on the number of poverty cases in West Java based on the SAR model are the percentage of the population without a diploma, the amount of expenditure per capita, and the percentage of open unemployment. Abstrak. Spatial Autoregressive Model (SAR) merupakan model pendekatan dari analisis regresi spasial. Analisis regresi spasial digunakan untuk mengetahui suatu hubungan berdasarkan informasi atribut dan informasi lokasi atau letak geografis. Penduga dari model SAR menggunakan metode penduga kemungkinan maksimum atau Maximum Likelihood Estimation (MLE). Tujuan dari penelitian ini adalah memodelkan regresi spasial SAR untuk mengetahui faktor-faktor yang mempengaruhi terjadinya kemiskinan di Jawa Barat. Untuk menjelaskan hubungan spasial antar lokasi pengamatan digunakan matriks pembobot spasial berdasarkam ketetanggaan (contiguity) yaitu matriks Queen Contiguity. Sebanyak 27 kabupaten/kota digunakan sebagai unit pengamatan dengan variabel dependennya (Y) adalah jumlah kasus kemiskinan dari setiap kabupaten/kota di Jawa Barat. Variabel independen yang digunakan merupakan faktor dugaan yang berhubungan dengan kasus kemiskinan. Variabel independennya (X) yaitu rata-rata upah pekerja formal, persentase penduduk tidak memiliki ijazah, persentase kesehatan penduduk, jumlah penduduk, jumlah pengeluaran per kapita, persentase tingkat pengangguran terbuka, dan UMR Jawa Barat. Variabel independen yang berpengaruh signifikan terhadap jumlah kasus kemiskinan di Jawa Barat berdasarkan model SAR, yaitu variabel persentase penduduk tidak memiliki ijazah, jumlah pengeluaran per kapita, dan persentase tingkat pengangguran terbuka.